Microbiological and Chemical Characteristics of Wet Coffee Fermentation Inoculated With Hansinaspora uvarum and Pichia kudriavzevii and Their Impact on Coffee Sensory Quality - Elhalis, Hosam; Cox, Julian; Frank, Damian; Zhao, Jian (Frontiers in Microbiology, 2021)
Hansinaspora uvarum and Pichia kudriavzevii were used as starter cultures to conduct inoculated wet fermentations of coffee beans, and their growth, metabolic activities and impact on the flavour, aroma and overall sensory quality of coffee were compared with spontaneous fermentation (control). H. uvarum and P. kudriavzevii dominated the fermentations, growing to maximum populations of about 10.0 log CFU/ml compared with 8.0 log CFU/ml in the spontaneous fermentation. The dominance of the inoculated yeasts led to faster and more complete utilization of sugars in the mucilage, with resultant production of 2-3 fold higher concentrations of metabolites such as glycerol, alcohols, aldehydes, esters, and organic acids in the fermented green beans. Cup tests showed coffee produced from the inoculated fermentations, especially with P. kudriavzevii, received higher scores for flavour, aroma and acidity than the control. The findings of this study confirmed the crucial role of yeasts in the wet fermentation of coffee beans and their contribution to high quality coffee, and demonstrated the potential H. uvarum and P. kudriavzevii as starter cultures in the process.